Determinan pengangguran muda: Studi di Negara ASEAN-5 2010-2019 - Nisa, Khoeru; Sugiharti, Rr. Retno (Nur Science Institute, 2022)
The role of youth is needed for the development of a country. However, unemployment is still a problem for young people currently. This study was conducted to analyze the effects of education, labor force participation rate (LFPR), economic growth, and population on youth unemployment in ASEAN-5 in 2010–2019. The method used is panel data regression with a fixed-effect model (FEM). The result of this study indicates that the variables of education and labor force participation rate (LFPR) have a positive and significant influence on youth unemployment. Meanwhile, economic growth and population variables have a positive and insignificant effect. By model, the model's equation in this study has met the criteria of goodness of fit. Therefore, increasing job opportunities, especially for youth as the nation's next-generation, must be a top priority to reduce unemployment and improve the quality of the young workforce by increasing training and competence in the workforce.